Unexpectedly high diversity of trypanosomes in small sub-Saharan mammals - Votýpka, Jan; Stříbrná, Eva; Modrý, David; Bryja, Josef; Bryjová, Anna; Lukeš, Julius (International journal for parasitology, 2022)
The extremely species-rich genus Trypanosoma has recently been divided into 16 subgenera, most of which show fairly high host specificity, including the subgenus Herpetosoma parasitizing mainly rodents. Although most Herpetosoma spp. are highly host-specific, the best-known representative, Trypanosoma lewisi, has a cosmopolitan distribution and low host specificity. The present study investigates the general diversity of small mammal trypanosomes in East and Central Africa and the penetration of invasive T. lewisi into communities of native rodents. An extensive study of blood and tissue samples from Afrotropical micromammals (1528 rodents, 135 shrews, and five sengis belonging to 37 genera and 133 species) captured in the Central African Republic, Ethiopia, Kenya, Malawi, Mozambique, Tanzania, and Zambia revealed 187 (11.2%) trypanosome-positive individuals. The prevalence of trypanosomes in host genera ranged from 2.1% in Aethomys to 37.1% in Lemniscomys. The only previously known trypanosome detected in our dataset was T. lewisi, newly found in Ethiopia, Kenya, and Tanzania in a wide range of native rodent hosts. Besides T. lewisi, 18S rRNA sequencing revealed 48 additional unique Herpetosoma genotypes representing at least 15 putative new species, which doubles the known sequence-based diversity of this subgenus, and approaches the true species richness in the study area. The other two genotypes represent two new species belonging to the subgenera Ornithotrypanum and Squamatrypanum. The trypanosomes of white-toothed shrews (Crocidura spp.) form a new phylogroup of Herpetosoma, unrelated to flagellates previously detected in insectivores. With 13 documented species, Ethiopia was the richest region for trypanosome diversity, which corresponds to the very diverse environments and generally high biodiversity of this country. We conclude that besides T. lewisi, the subgenus Herpetosoma is highly host-specific (e.g., species parasitizing the rodent genera Acomys and Gerbilliscus). Furthermore, several newly detected trypanosome species are specific to their endemic hosts, such as brush-furred mice (Lophuromys), dormice (Graphiurus), and white-toothed shrews (Crocidura).
Keywords: Biodiversity; Trypanosomiasis; Herpetosoma; Etiopie; RNA, Ribosomal, 18S; rejskovití; trypanozomiáza; Ethiopia; Murinae; Zoonosis; Rodents; Animals; Africa; zvířata; Gerbillinae; Shrews; RNA ribozomální 18S; Host specificity; Trypanosoma